До літології нижньоеоценових відкладів північно-західного шельфу Чорного моря - Ревер, В. (Геологія і геохімія горючих копалин, 2010)
На основі літологічного вивчення нижньоеоценових відкладів північно-західного шельфу Чорного моря встановлено три літологічні типи розрізів: карбонатний,
глинисто-карбонатний та теригенний. Вивчено петрографічні особливості товщотворних компонентів, ареали їхнього домінуючого розвитку в розрізах теригенних
(Одесько-Безіменний) та карбонатних (Фланговий, Шмідтівський, Кримський) порід. Results of drilling on a shelf of the Black Sea and adjoined territories (in particular in
Kerch peninsula, the Ukrainian and Bulgarian shelf, and a north-western part of the Caucasus) testify to prospects of oil and gas presence in the Eocene deposits. The territory of
researches is placed within Karkinit-Northtern Crimea depression, where in connection
with small core recovery the Eocene deposits remain insufficiently studied. Therefore for
a substantiation of perspectivity of this sedimentary complex it is necessary to conduct its
all-round studying, in particular its lithological peculiarities.